2014
DOI: 10.3389/fphys.2014.00298
|View full text |Cite
|
Sign up to set email alerts
|

Regionalizing muscle activity causes changes to the magnitude and direction of the force from whole muscles—a modeling study

Abstract: Skeletal muscle can contain neuromuscular compartments that are spatially distinct regions that can receive relatively independent levels of activation. This study tested how the magnitude and direction of the force developed by a whole muscle would change when the muscle activity was regionalized within the muscle. A 3D finite element model of a muscle with its bounding aponeurosis was developed for the lateral gastrocnemius, and isometric contractions were simulated for a series of conditions with either a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…The simulations in this study (M1-M6) were for muscle with uniform distributions of activity and intramuscular fat. It should be remembered that muscle force additionally depends on regional variations in muscle activity [22,42], fat distribution (figure 4) and fibre-type composition [43,44], and that muscle contribution to joint torque also depends on its moment arm that can vary with ageing and obesity [45,46]. Nonetheless, the results from this study show that the inclusion of intramuscular fat and the basematerial properties of the muscle tissue have an important effect on muscle force.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The simulations in this study (M1-M6) were for muscle with uniform distributions of activity and intramuscular fat. It should be remembered that muscle force additionally depends on regional variations in muscle activity [22,42], fat distribution (figure 4) and fibre-type composition [43,44], and that muscle contribution to joint torque also depends on its moment arm that can vary with ageing and obesity [45,46]. Nonetheless, the results from this study show that the inclusion of intramuscular fat and the basematerial properties of the muscle tissue have an important effect on muscle force.…”
Section: Discussionmentioning
confidence: 63%
“…The neo-Hookean strain energy for the fat (W fat ) was adopted based on modelling work on human breast tissue [31] and is defined as where I 1 is the first invariant of the Cauchy-Green deformation tensor. The adipose tissue (fat) had a larger stiffness than the isotropic muscle base material (figure 2) for the lean muscle (eqn 8 in [22]). However, fat stiffness was less than the passive response of the whole muscle tissue that includes both the base-material and fibre properties (figure 2).…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, modelling studies demonstrate that greater aponeurosis stiffness results in a reduction in its stretch that decreases muscle fibre strain (Rehorn & Blemker, 2010;Rahemi et al 2014). Conceptually, our method reflects the elongation of distal (to the ultrasound measurement site) tendinous tissues (aponeurosis-tendon).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the inability of the models to predict and operate at large aponeurosis strains may be a factor influencing such errors. Recently, we have shown that the aponeurosis stiffness and stretch greatly influence the extent to which the muscle pennation changes during contraction and the magnitude of the whole muscle force (Rahemi et al, 2014). Understanding the role and contribution of the aponeurosis compliance is a necessary aspect of understanding the structure and dynamics of muscle contraction (Kawakami et al, 1998;Rahemi et al, 2014).…”
Section: Modelmentioning
confidence: 99%